NEARPOD BIKIN GURU TIDAK REPOT - sri nurhasanti (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
This writing is formerly in the intention to make the writer easy in her teaching and learning in her class in the early of the existence of Covid – 19, when the students were too lazy to engage with the teaching and learning material. In order to solve this problem, then the teacher tried to find out the best teaching and learning media to make the students happy and enjoyable with the English lesson. Finally, the teacher found Nearpod as the best way to engage the students with the learning and makes them interested in learning English.   If formerly the active participation of the students in the teaching and learning is less than 50 %, after using this application, the involvement of the students’ participation increase as well as the result of the average class score. Formerly, the average score is between 78- 85 for grade IX F from the average minimum score 76. Besides that, the average scores of the other classes also increase. The number of students’ passing grade is also increasing from the former time. Before using this application, there are only about 16 -20, however, now it becomes around 29 even 32. The average score of every class is also increasing from 50 – 60, becomes 78 – 85. The weakness of this application is in the internet access. However, to cover this problem, the teacher still can send the asynchronous link to join back in another time.